Work-home and home-work conflict and voluntary turnover: A conservation of resources explanation for contrasting moderation effects of on- and off-the-job embeddedness - Rubenstein, Alex L.; Peltokorpi, Vesa; Allen, David G. (Journal of vocational behavior, 2020)
Although greater on- and off-the-job embeddedness are both predominately assumed to constrain voluntary turnover, we theorize how greater off-the-job embeddedness could lead employees facing high interrole conflict to be more likely to quit, though greater on-the-job embeddedness would reduce turnover likelihood in the face of conflict. Accordingly, we hypothesized that higher off-the-job embeddedness would strengthen the positive relationship between interrole conflict and turnover, whereas we expected higher on-the-job embeddedness would weaken the positive relationship between interrole conflict and turnover. To ground these diverging perspectives, we adopted the conservation of resources theory approach to job embeddedness (Kiazad, Holtom, Hom, & Newman, 2015), arguing that when employees report significant interrole conflict between work and home domains, they focus personal resources into those domains in which they are highly embedded (i.e., on- or off-the-job). We further hypothesized that the strength of on- and off-the-job embeddedness moderation effects would differ depending on the direction in which conflict is experienced (i.e., from work-to-home or from home-to-work). Data from 717 working mothers in Japan, with responses collected at three time points over 14 months, largely supported these hypotheses along with some interesting nuance. •Job embeddedness moderated work-home and home-work conflict-turnover effects.•Higher on-the-job embeddedness weakened the effect of conflict on turnover.•Higher off-the-job embeddedness strengthened the effect of conflict on turnover.•Off-the-job embeddedness more strongly moderated work-home conflict-turnover.•On-the-job embeddedness more strongly moderated home-work conflict-turnover.